2019
DOI: 10.3389/fphar.2019.00072
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine Directly Inhibits α6-Containing Nicotinic Acetylcholine Receptors in Human SH-EP1 Cells and Mouse VTA DA Neurons

Abstract: Alpha6-containing nicotinic acetylcholine receptors are primarily found in neurons of the midbrain dopaminergic (DA) system, suggesting these receptors are potentially involved in drug reward and dependence. Here, we report a novel effect that cocaine directly inhibits α6N/α3Cβ2β3-nAChR (α6*-nAChRs) function. Human α6*-nAChRs were heterologously expressed within cells of the SH-EP1 cell line for functional characterization. Mechanically dissociated DA neurons from mouse ventral tegmental area (VTA) were used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…This is consistent with previous findings using FSCV and is due to off target cocaine inhibition of nAChRs, which contribute significantly to striatal dopamine release. This off target cocaine inhibition of nAChRs was first shown electrophysiologically 16,17 and then with striatal FSCV 18,19 .…”
Section: Differential Regulation Of Dlight Photometry and Fscv Dopami...mentioning
confidence: 86%
“…This is consistent with previous findings using FSCV and is due to off target cocaine inhibition of nAChRs, which contribute significantly to striatal dopamine release. This off target cocaine inhibition of nAChRs was first shown electrophysiologically 16,17 and then with striatal FSCV 18,19 .…”
Section: Differential Regulation Of Dlight Photometry and Fscv Dopami...mentioning
confidence: 86%
“…Nicotine increases mesolimbic dopamine release via nicotinic acetylcholine receptors (nAChRs), and there is evidence that suggests cocaine acts as a nAChR antagonist (Acevedo-Rodriguez, Zhang, Zhou et al, 2014; Chen, Gao, Ma et al, 2019). Therefore nAChRs may represent a target of interest for future studies of combined cocaine and nicotine self-adminsitration.…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral experiments showed that local injection of a selective α 4 β 2 nAChR antagonist (dihydro-β-erythroidine, DHβE) into the ventral tegmental area (VTA) prevents cocaine-induced locomotor activity [ 14 ], while the α 7 -selective antagonist methyllycaconitine (MLA) did not alter cocaine-induced behavioral sensitization [ 15 ]. Recently, nAChRs containing the α 6 subunit (α 6 * nAChRs), but not those containing the α 4 subunit, were shown to play a role in the induction of cocaine-conditioned reward [ 16 ], and we have recently reported that cocaine blocks human α 6 * nAChRs expressed in human SH-EP1 cells [ 17 ]. The α 3 β 4 nAChR may also be an important target that mediates the effects of cocaine.…”
Section: Introductionmentioning
confidence: 99%